Distrianthes exxonmobilensis (Loranthaceae), a new species in a formerly monotypic genus from Papua New Guinea - Takeuchi, Wayne (Phytotaxa, 2015)
Distrianthes exxonmobilensis is described from karst environments along the PNG LNG Pipeline in southern New Guinea. It is the second species in a genus previously regarded as monotypic. The new loranth is distinguished by an inflorescence reduced to a single flower or triad, and by the geographic disjunction from previous generic localities.